Mitochondrial DNA copy number in peripheral blood of IgA nephropathy: a cross-sectional study - Jiaqi Liu; Rong Wang; Ning Luo; Zhibin Li; Haiping Mao; Yi Zhou (Renal Failure)
Mitochondrial DNA (mtDNA) copy number (CN) is a biomarker of mitochondrial function and has been reported associated with kidney disease. However, its association with IgA nephropathy (IgAN), the most common cause of glomerulonephritis (GN), has not been evaluated. We included 664 patients with biopsy-proven IgAN and measured mtDNA-CN in peripheral blood by multiplexed real-time quantitative polymerase chain reaction (RT-qPCR). We examined the associations between mtDNA-CN and clinical variables and found that patients with higher mtDNA-CN had higher estimated glomerular filtration rate (eGFR) (r = 0.1009, p = .0092) and lower serum creatinine (SCr), blood urea nitrogen (BUN), and uric acid (UA) (r=−0.1101, −0.1023, −0.07806, respectively, all p values <.05). In terms of pathological injury, mtDNA-CN was higher in patients with less mesangial hypercellularity (p = .0385, M0 vs. M1 score by Oxford classification). Multivariable logistic regression analyses also showed that mtDNA-CN was lower for patients with moderate to severe renal impairment (defined as eGFR < 60 mL/min/1.73 m2) vs. mild renal impairment, with the odds ratio of 0.757 (95% confidence interval: 0.579–0.990, p = .042). In conclusion, mtDNA-CN was correlated with better renal function and less pathological injury in patients with IgAN, proposing that systemic mitochondrial dysfunction may be involved in or reflect the development of IgAN.